The Routledge companion to Iberian studies - Muñoz-Basols, Javier; Lonsdale, Laura; Delgado Morales, Manuel (Routledge, 2017)
The Routledge Companion to Iberian Studies takes an important place in the scholarly landscape by bringing together a compelling collection of essays that reflect the evolving ways in which researchers think and write about the Iberian Peninsula. Features include: • A comprehensive approach to the different languages and cultural traditions of the Iberian Peninsula; • Five chronological sections spanning the period from the Middle Ages to the 21st century; • A state-of-the-art account of the field, reaffirming Iberian Studies as a dynamic and evolving discipline with promising areas for future research; • An array of topics of an interdisciplinary nature (history and politics, language and literature, cultural studies and visual arts), focusing on the cultural distinctiveness of Iberian traditions; • New perspectives and avenues of inquiry that aim to promote a comparative mode within Iberian Studies and Hispanism. The fifty authoritative, original essays will provide readers with a diverse cross-section of texts that will enrich their knowledge of Iberian Studies from an international perspective.